ANALISIS KESALAHAN MAHASISWA PRODI PENDIDIKAN MATEMATIKA FAKULTAS TARBIYAH IAIN AR-RANIRY DALAM MATA KULIAH TRIGONOMETRI DAN KALKULUS 1 - Zainal Abidin (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2012)
There are many students of Mathematic Education Department in Tarbiyah Faculty of IAIN Ar-Raniry got difficulties to learn Calculus I. It is proven by many students fail the Calculus class. One of the causes is they did not really master the concept of trigonometric as one of the prerequisite of calculus I. Therefore, we need to know and analyze the type of mistaken they made and the tendency to produce the mistakes in answering the trigonometric’s question. In this research, data were collected through interview and questionnaire. Then, they were analyzed by using descriptive statistic. The result shows that the mistaken done by students in answering the trigonometric questions as the prerequisite of Calculus 1covers the mistake of facts, skills, concept and principles. Meanwhile, the tendency of doing the mistaken coming from principle misconception due to lack of understanding of trigonometric concept.